An equation of state for the liquid phase - Subbarao, D. (Trans Tech Publications Ltd, 2014)
Developments in Equation of State for gases have enabled estimation of properties of gases with reasonable accuracy. Equation of State for liquid phase is developed in this note to explain dependence of density of liquid on temperature through latent heat vaporization and specific heat of the liquid. The model is validated with data on some common liquids. Â© 2014 Trans Tech Publications, Switzerland.